Pendidikan Islam pada Pengguna Narkoba di Klinik Pratama BNN Kabupaten Temanggung - Nurul Khasanah Nurul; Sigit Tri Utomo; Ana Sofiyatul Azizah (Yayasan Azhar Amanaa Yogyakarta, 2023)
This study aims to determine the implementation of Islamic education for drug users at the BNN Pratama Clinic, Temanggung Regency. This type of research is field research with qualitative methods. Data collection techniques used in this study were observation, interviews, and documentation. Data were analyzed using data reduction, data presentation, and drawing conclusions. The results of the study found that the application of Islamic education in drug rehabilitation is by teaching the main teachings in Islamic education, namely faith education, moral education, and worship education. Supporting factors in rehabilitation activities are support from family, commitment from clients or users to recover, social environmental factors. While the inhibiting factors for the implementation of Islamic education for drug users are limited time, poor character from clients or users, and lack of support from family